Postać Elżbiety Batory w historiografii - Szabelski, Adam (Studia Europaea Gnesnensia, 2014)
The aim of the paper is to present the figure of Elisabeth Bathory as it is shown in historiography and to confront the myths surrounding her person with the findings of the researchers, especially Hungarian scholars who studied her life. It has been shown that Elisabeth Bathory fell victim to the plot of the palatine György Turzó, probably instigated by the court in Vienna. Unfortunately, Polish historians have so far neglected to address this issue in their research.